Globalization and the Need for Strategic Government-Industry Cooperation in the Philippine Automotive Industry - Rafaelita M. Aldaba (Philippine Institute for Development Studies (PIDS), 2008)
The industry's lack of competitiveness, absence of economies of scale and a weak supply base are the fundamental issues that must be addressed in order to strengthen the industry and integrate it with regional production networks of foreign automakers. The entry of cheap, smuggled second-hand vehicles has put tremendous pressure on the industry. Immediate government action to address smuggling and design a coherent set of policies and a comprehensive strategy to improve industry competitiveness is urgently needed. A temporary adjustment program is necessary to help both assemblers and parts makers face competition in the future and more importantly, in preparation for the implementation of zero tariffs under the AFTA in 2010. If smuggling continues and our competitiveness remains weak, the auto industry may just be a thing of the past as auto companies shift from CKD to CBU operations. This is the reality of doing business under the globalization age.
Keywords: 330; globalization; competitiveness; production networks; Philippine automotive industry; Kfz-Industrie; Globalisierung; Internationaler Wettbewerb; Industriepolitik; Philippinen